Synthesis, EPR and Optical Properties of Oxovanadium(IV) Complexes with Tris(2-aminoethyl amine) and Substituted Imidazoles - Singh, P.K. (Asian Journal of Chemistry, 2016)
The synthesis, characterization with EPR and electronic absorption spectra of [VO(tren)](BPh4)2, [VO(tren)ImH](BPh4)2, [VO(tren)M-ImH](BPh4)2 and [VO(tren)E-ImH](BPh4)2 using tris(2-aminoethyl amine), 2-methylimidazle and 2-ethylimidazole as ligands have been reported.